2018
DOI: 10.3390/medicina54050074
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Antibiotic Usage at the Children’s Clinical University Hospital in Riga, Latvia

Abstract: Background and objectives: Many pediatric patients have been treated with antibiotics during their hospitalization. There is a need to improve antibiotic prescribing for pediatric patients because many of these prescriptions are inappropriate. Antibiotic consumption analysis was conducted at the Children’s Clinical University Hospital to identify targets for quality improvement. Materials and Methods: A one day cross-sectional point prevalence survey (PPS) was conducted in May and November 2011–2013 using a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
2
5
0
1
Order By: Relevance
“…The major route of administration of the antibiotics in this present study was intravenous. This is also similar to the findings of the Riga study where 76 to 86% of all prescriptions were via the intravenous route [16]. In practice, the intravenous route is usually used in the treatment of severe systemic infections in hospitalized patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The major route of administration of the antibiotics in this present study was intravenous. This is also similar to the findings of the Riga study where 76 to 86% of all prescriptions were via the intravenous route [16]. In practice, the intravenous route is usually used in the treatment of severe systemic infections in hospitalized patients.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to the reports of another study in South-east Nigeria (78.6%) [14] and Uganda (79%) [15]. The prevalence of antibiotic use in this present study is however higher than the findings of Sviestina and Mozgis [16] who observed that only between 26% to 38% of inpatients in their point prevalence study in Childrens' Clinical university hospital, Riga, Latvia (Northern Europe) were receiving antibiotics. The likely reason for the difference in the prevalence of antibiotic use may be because, in the Riga study, the hospital has an established ward-based clinical pharmacist service.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…[14][15][16] It was more as compared to studies done in Latvia (26-38%), Brazil (24.4%) and Spain (16.5%). [17][18][19] Study done in USA was a very large study which showed percentage of antibiotic use of 38-72% in different states of USA with mean use of 60%. 20 On comparing our study with similar Indian studies (from Andhra Pradesh, Puducherry and Kolkata percentage of encounter with antibiotic was 50.05, 60 and 79.82% respectively), our antibiotic usage was quite less.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of this type of program have not been studied in-depth, and few comparisons can be found in literature. Studies monitoring the consumption of antibiotics predominate in different contexts, such as hospitals [ 14 , 15 ] and primary care [ 16 , 17 , 18 , 19 ]. All of them conclude with the recommendation not only to introduce health policies to reduce the consumption of these drugs but also to quantify the results.…”
Section: Introductionmentioning
confidence: 99%